2004
DOI: 10.1179/174327804x13884
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribocorrosion properties of HVOF sprayed WC–Co coatings

Abstract: HVOF technology has been proposed in recent years for the production of engineered cermet coatings suitable for the replacement of hard chromium surface treatments of mechanical components, for aeronautical and automotive applications. The aim of this study has been to compare the mechanical and tribocorrosion properties of WC-Co cermet coatings fabricated with different processing parameters, to optimise the spraying process by evaluating the dependence of the macroscopic coating properties on the spraying pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…The average roughness of uncoated mild steel, SS202, and SS304 is observed as 2.45, 1.35, and 1.38 µm, whereas the values were 4.89, 4.63, and 4.58 µm after deposit coating. The investigators suggested that cutting, fracture, and abrasion are the major modes of erosion wear mechanisms that are relevant to slurry pipelines [2,3,13,14]. The eroded images of WC-10 Co 4 Cr-coated mild steel, SS202, and SS304 with EDS (energy dispersive spectroscopy) are shown in Figures 6-8.…”
Section: Visual Examination Of Eroded Coated Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The average roughness of uncoated mild steel, SS202, and SS304 is observed as 2.45, 1.35, and 1.38 µm, whereas the values were 4.89, 4.63, and 4.58 µm after deposit coating. The investigators suggested that cutting, fracture, and abrasion are the major modes of erosion wear mechanisms that are relevant to slurry pipelines [2,3,13,14]. The eroded images of WC-10 Co 4 Cr-coated mild steel, SS202, and SS304 with EDS (energy dispersive spectroscopy) are shown in Figures 6-8.…”
Section: Visual Examination Of Eroded Coated Surfacesmentioning
confidence: 99%
“…These coatings can provide a hard layer of carbides, oxides, and nitrides of Cr, W, Al, and Ti [10,11]. The high-velocity oxy-fuel (HVOF) technique can be applied to deposit coatings with high cohesive strength and superior mechanical properties [10][11][12][13][14]. In the present work, erosion wear behavior of three piping materials, namely, mild steel, SS202, and SS304, have been analyzed with and without a HVOF-sprayed WC- 10 Co 4 Cr coating.…”
Section: Introductionmentioning
confidence: 99%
“…low pH) from the bulk conditions and induce crevice corrosion, which in turn contributes to increased C e levels. The influence of the spraying parameters (spraying distance, barrel length and kerosene flow rate) on the tribo-corrosion performance of HVOF sprayed WC-17Co coatings has been studied by Valentinelli et al [51]. They also found that binder dissolution controlled wear-corrosion levels and therefore coating compositions should be designed with reference to the relevant Pourbaix diagrams (potential versus pH regime maps based on thermodynamic considerations only) to select compositions that are passive in the service environment and in addition have strong repassivation tendencies.…”
Section: Thermally Sprayed Coatingsmentioning
confidence: 99%
“…Bartuli et al [9] in order to force the flow equation simulation WC-Co Nano HVOF spray coating process in the best parameters, explore the combustion flame and particle flow of hot gas chemical and dynamical properties of WC-Co coated nanostructures affected layer by abrasion tests found nanostructure coating having a low coefficient of friction, and having high hardness and high fracture toughness.…”
Section: Introductionmentioning
confidence: 99%